Surface expression of the hRSV nucleoprotein impairs immunological synapse formation with T cells. - Céspedes, P; Bueno, S; Ramírez, B; Gomez, R; Riquelme, SA; Palavecino, C; Mackern-Oberti, J; Mora, J; Depoil, D; Sacristán, C; Cammer, M; Creneguy, A; et al. (National Academy of Sciences, 2014)
Human respiratory syncytial virus (hRSV) is the leading cause of bronchiolitis and pneumonia in young children worldwide. The recurrent hRSV outbreaks and reinfections are the cause of a significant public health burden and associate with an inefficient antiviral immunity, even after disease resolution. Although several mouse- and human cell-based studies have shown that hRSV infection prevents naïve T-cell activation by antigen-presenting cells, the mechanism underlying such inhibition remains unknown. Here, we show that the hRSV nucleoprotein (N) could be at least partially responsible for inhibiting T-cell activation during infection by this virus. Early after infection, the N protein was expressed on the surface of epithelial and dendritic cells, after interacting with trans-Golgi and lysosomal compartments. Further, experiments on supported lipid bilayers loaded with peptide-MHC (pMHC) complexes showed that surface-anchored N protein prevented immunological synapse assembly by naive CD4(+) T cells and, to a lesser extent, by antigen-experienced T-cell blasts. Synapse assembly inhibition was in part due to reduced T-cell receptor (TCR) signaling and pMHC clustering at the T-cell-bilayer interface, suggesting that N protein interferes with pMHC-TCR interactions. Moreover, N protein colocalized with the TCR independently of pMHC, consistent with a possible interaction with TCR complex components. Based on these data, we conclude that hRSV N protein expression at the surface of infected cells inhibits T-cell activation. Our study defines this protein as a major virulence factor that contributes to impairing acquired immunity and enhances susceptibility to reinfection by hRSV.